EVOLUTION OF ROBOTIC-ASSISTED SURGERY: A SYSTEMATIC REVIEW OF OUTCOMES IN MAJOR SURGICAL SPECIALTIES - Dr Gulshan Kumar; Dr Vikram Singh yadav (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Robotic assisted surgery has changed modern surgical practice, increasing precision and decreasing invasiveness. In this systematic review, evaluate its evolution focusing on perioperative outcomes across major surgical specialties. The greater blood loss, shorter hospital stay, and fewer complications that robotic systems show compared to open surgery (OS) make them representative of a superior form of treatment. Overall, however,  remain less conclusive than minimally invasive surgery (MIS) because the complication rates are similar and due to longer operative times. High costs, steep learning curves, and limited accessible pose key challenges in the uptake. These systems are candidates for improvement by emerging technologies, like artificial intelligence (AI), haptic feedback, and augmented reality. Overcoming these technical challenges will require cost effective, efficient solutions to bring robotic surgery further and to integrate into healthcare in an equitable way.